Pengembangan Pembelajaran Kontekstual Guru SMP Muhammadiyah 2 Kota Batu Berbasis Ekologi Sosial - Purwati Anggraini; Hidayah Budi Qur’ani (Jurnal Pengabdian Pada Masyarakat, 2020)
DEVELOPMENT OF CONTEXTUAL LEARNING IN TEACHERS OF SMP MUHAMMADIYAH 2 BATU CITY BASED ON SOCIAL ECOLOGY. The problem faced by Batu Muhammadiyah Middle School students is that students have not been able to fully understand learning. They have not been able to understand and apply the learning material in real life. This is because the teacher is oriented to the completion of the material and the values ​​that must be achieved by students, both academic grades and values ​​related to character. The series of activities carried out are (1) input from program participants, (2) activities carried out in the form of training in making contextual learning media based on social ecology, and (3) the results achieved are the soft skills of teachers in developing contextual learning. In addition to soft skills, the teachers of Junior High School Muhammadiyah 2 Batu also have an awareness that fun learning can give students a complete understanding, so this increases student grades. Students also become more skilled in applying the knowledge they obtain to their daily lives.